Academic Flow of Vocational Students: The Role of Self Regulated Learning and Task Commitment - Yusro, Maghfirul; Khotimah, Siti Khorriyatul (International Conference on Sustainable Health Promotion, 2023)
This study, which aims to determine whether there is an effect of self-regulated learning and task commitment to academic flow on SMK YPM 1 students, is a correlational quantitative study using multiple linear regression statistical analysis. The subjects of this study were 210 students of SMK YPM 1 Sidoarjo. The research instruments used are the Academic Flow Scale, the Self Regulated Learning Scale and the Task Commitment Scale which are valid and reliable. From this study it is known that self regulated learning and task commitment have a significant effect on student academic flow partially and simultaneously. With a significance value of 0.000 <0.05 which indicates that selfregulated learning and task commitment together have a significant effect to the academic flow of YPM SMK students 1 Sidoarjo. With a regression coefficient value of 0.881, it is known that selfregulated learning and task commitment variables contribute 88.1% to students' academic flow, while the remaining 11.9% is influenced by other variables. Future researchers are expected to study other variables that affect students' academic flow.